Covid-19 Learning Loss and Recovery: Panel Data Evidence from India - Abhijeet Singh; Mauricio Romero; Karthik Muralidharan (Center for Economic Studies and ifo Institute (CESifo), 2022)
We use a panel survey of ∼19,000 primary-school-aged children in rural Tamil Nadu to study 'learning loss' after COVID-19-induced school closures, and the pace of recovery after schools reopened. Students tested in December 2021 (18 months after school closures) displayed learning deficits of ∼0.7σ in math and 0.34σ in language compared to identically-aged students in the same villages in 2019. Two-thirds of this deficit was made up within 6 months after school reopening. Further, while learning loss was regressive, the recovery was progressive. A government-run after-school remediation program contributed ∼24% of the cohort-level recovery, and likely aided the progressive recovery.
Keywords: H52; I21; I25; O15; 330; Covid-19; school closures; learning loss; recovery